2012
DOI: 10.1007/s00404-012-2518-9
|View full text |Cite
|
Sign up to set email alerts
|

Consent for gynaecological procedure: what do women understand and remember?

Abstract: A third of women who had planned gynaecology procedure do not recall any risk associated with the procedure. Provision of information leaflet did not make any consistent difference.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 13 publications
2
7
0
1
Order By: Relevance
“…This is particularly so within the ‘Affirmative’ group where higher level of formal education is associated with higher proportion of appropriate recall (Tables 2 , 3 , 4 ). Similar results were obtained by Pathak et al among women [ 28 ] and Dahl et al among parents of children scheduled for emergency procedures [ 29 ]. Appropriate recall of risks of planned surgeries is generally poor at 21.7% of obtained responses.…”
Section: Discussionsupporting
confidence: 89%
“…This is particularly so within the ‘Affirmative’ group where higher level of formal education is associated with higher proportion of appropriate recall (Tables 2 , 3 , 4 ). Similar results were obtained by Pathak et al among women [ 28 ] and Dahl et al among parents of children scheduled for emergency procedures [ 29 ]. Appropriate recall of risks of planned surgeries is generally poor at 21.7% of obtained responses.…”
Section: Discussionsupporting
confidence: 89%
“…It may also represent a challenge in the complicated consent process for pelvic reconstructive surgery. This is supported by recent studies showing deterioration of patient understanding of surgical counseling hours 6 or weeks after gynecologic and mid-urethral sling surgery 7 .…”
Section: Commentmentioning
confidence: 56%
“…Studies have demonstrated poor comprehension after doctor visits; therefore, it would be interesting to see if the misperceptions regarding mesh were dispelled after a visit with one of our specialists or if they persisted and this is a potential for future research. [9][10][11] Also most participants included for analysis presented with UI. While the subsequent FDA public health notification focused on transvaginal mesh for POP, a limitation is that our study had a primary UI patient population base.…”
Section: Commentmentioning
confidence: 99%